The multifaceted role of IL-12 in cancer - Um e Habiba; Mussarat Rafiq; Muhammad Babar Khawar; Bismillah Nazir; Gulfam Haider; Nadia Nazir (Advances in Cancer Biology - Metastasis, 2022)
Interleukin-12 is a heterodimeric cytokine having many family members IL-23, IL-27, IL-35, and recently discovered IL-39, produced by macrophages and dendritic cells. IL-12 is an effector cytokine and engages in anti-tumor and many immunotherapies as IL-12 DNA expression, Th1 helper cells, and natural killer cells. IL-12 stimulates interferon γ (INF-γ) synthesis by the activation of STAT4 which then differentiates the Th1 helper cells with the T-bet transcription, playing an important role in cancer treatment. This review focuses on the role of IL-12 family as an antitumor agent as understanding the biology and molecular mechanism of IL-12 family members is crucial for designing new therapeutic strategies against different cancers.